Massive Hemorrhages in Pregnant Women with Placenta Previa and Accreta: a Transfusiologist’s View - T. A. Fyodorova; O. V. Rogachevsky; A. V. Strelnikova; A. Y. Korolyov; A. A. Vinitsky (Неотложная медицинская помощь, 2018)
Abstract The aim of this study was to estimate volumes of blood loss and infusion and transfusion therapy during Cesarean section in pregnant women with placenta previa and accreta.Material and methods Тhe study group consisted of 15 patients with placenta previa and accreta. The delivery period was 32–36 weeks. We used clinical and laboratory techniques and special methods of investigation. The analysis of pregnancy course, bleeding volumes, infusion and transfusion therapy, hemostasis system parameters and hemogram was carried out.Results Тhe mean age of pregnant women was 33.8±4.3 years. All pregnant women underwent fundal Cesarean section. In 80% of women, we performed Cesarean section and metroplasty. In 20% of women, Cesarean section and hysterectomy were performed. The volume of intraoperative blood loss ranged from 750 ml to 6,000 ml and averaged 2,471.4±1,528.5 ml. The volumes of crystalloid solutions were 1,361.53±1,052.40 of Sterofundin, and 688.4±123.5 ml of other solutions. In 80% of patients, Gelofusine was administered (969.66±351.86 ml on the average), as well as Geloplasma (620.8±124.8 ml on the average). The volume of HES solutions 6% 130/04 was 744.4±120.45 ml on the average. FFP in the amount of 1,526.7±762.83 ml was transfused to 60% of women. The mean dose of tranexamic acid was 2.6±0.84 g. The factor rFVIIa was administered in three patients in the dose of 90 mcg/kg. Prothrombin complex concentrate 1200 IU was administered in three patients. The volume of reinfused autoerythrocytes was 793.7±424.17 ml on the average. The volume of donor red blood cells during the operation amounted to 775.12±120.2 ml.Conclusion Pregnant patients with placenta previa and accrete represent a high-risk group for the development of massive coagulopathic bleeding and postoperative complications. These patients should deliver on a routine basis at the high-tech institutions of obstetric care. The adequate, timely infusion and transfusion maintenance of surgical intervention with this pathology, using modern blood-saving technologies, transfusion of sufficient volumes of blood components, inhibitors of fibrinolysis, coagulation factors, modern balanced crystalloid and colloidal solutions plays a important role in implementation of organpreserving tactics.